The Effects of Cancer - Related Fatigue Symptom Management Program through Walking Exercise and Pray Therapy on Quality of Life of Breast Cancer Patients - ลพสุนทร, ณัชนรี; นิมิตรอานันท์, นงพิมล; ฮุ่นตระกูล, สุธีรา (Journal of The Royal Thai Army Nurses, 2018)
This quasi – experimental research three group pretest - posttest design was aimed to compare results of symptom management program through walking exercise and pray therapy on quality of life of breast cancer patients after post chemotherapy treatment. The program was developed based on the Symptom Management Model. The 31 subjects were the patients utilized service at a private hospital in Samut Sakhon Province. They were divided into three groups by simple random and were invited to either programs: walking exercise, pray therapy and walking exercise with pray therapy for eight weeks. The data were collected from July to August 2016. The data collecting instruments were consisted of demographic questionnaire, cancer – related fatigue and quality of life perception. Their reliability were presented at .96 and .87 respectively. These data were analyzed by using descriptive statistics, Wilcoxon Signed Rank test and the Kruskal-Wallis test. The results revealed that after the sample joined the program, all groups had significantly decreased cancer – related fatigue score and increased quality of life perception score than before joining the program (p < .05). However, when compared among those 3 groups, there was no significant of cancer – related fatigue score and quality of life perception score after joining the program. The research suggested that professional nurses and healthcare team should concern the benefits of cancer – related fatigue relief through walking exercise and pray therapy according to holistic approach services, and lastly quality of life improvement.